Bacillus sp. PM31 harboring various plant growth-promoting activities regulates Fusarium dry rot and wilt tolerance in potato. Issue 2 (28th January 2023) - Mehmood, Shehzad; Khatoon, Zobia; Amna,; Ahmad, Iftikhar; Muneer, Muhammad Atif; Kamran, Muhammad Aqeel; Ali, Javed; Ali, Baber; Chaudhary, Hassan Javed; Munis, Muhammad Farooq Hussain
ABSTRACT: Fusarium solani ( F. solani ) is one of the most important pathogenic fungi, that cause Fusarium dry rot and Fusarium wilt in potato, responsible for low potato yield globally. However, the mechanistic understanding regarding the biocontrol of F. solani remains largely unknown. Here, we investigated the plant growth-promoting and antagonistic capability of Bacillus sp. PM31 against phytopathogen F. solani. The Bacillus sp. PM31, isolated from field-grown potato was analyzed for plant growth-promoting and extracellular enzyme activities. The strain PM31 exhibited phosphate, zinc, and potassium solubilization, nitrogen fixation, siderophore, exopolysaccharides production, and extracellular enzyme activities. The mycelial growth of F. solani was inhibited by strain PM31 with inhibition coefficient of 47.5. Under the storage conditions, inoculation of strain PM31 minimized the development of dry rot symptoms by 57% as compared to uninoculated diseased tubers. Under greenhouse conditions, inoculation of strain PM31 enhanced potato plant growth under fungal stress, while reduced the development of wilting, foot rot, chlorosis, and necrosis of inoculated potato plants by 92%, 75%, 64%, and 82%, respectively, as compared to diseased plants. Results inferred that the inoculation of native antagonistic Bacillus sp., PM31, could aid in global food security through biocontrol of important potato diseases viz . Fusarium dry rot and Fusarium wilt.